PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MTS NEGERI 1 SUMENEP - Gustuningtiyas M, Mauviroh; ROESMININGSIH, ERNY (Inspirasi Manajemen Pendidikan, 2019)
Abstract This study aims to describe the role of principals in improving teacher performance at Sumenep 1 MTsN which includes several sub-activities. The research approach used is a descriptive qualitative approach with a case study design (case study). Data collection techniques are carried out by observation, interviews, and documentation studies. The technical analysis of the data used includes data condensation, data presentation, and conclusion / verification. The validity test of the data is done through a credibility test which includes source triangulation, technical triangulation, time triangulation, and member check; external validity test; dependability; and confirmation. The results of the study show that the role of the principal in improving teacher performance was the principal as a leader, namely making indicators of success, empowering management and teachers and awarding rewards, principals as motivators through giving motivation and fostering education staff discipline, principals as educators educator) that is making agreed targets, conducting target socialization and completing teacher facilities. This role has an effect on improving teacher performance, even though it is not maximized and still needs to be evaluated and the principal needs to continue to improve teacher performance in order to advance the quality of school education. Keywords: the role of schools, teacher performance Abstrak Penelitian ini bertujuan untuk mendeskripsikan peran kepala sekolah dalam meningkatkan kinerja guru di MTsN 1 Sumenep yang mencakup beberapa sub kegiatan. Pendekatan penelitian yang digunakan adalah pendekatan kualitatif deskriptif dengan rancangan penelitian studi kasus (case study). Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan studi dokumentasi. Teknis analisis data yang digunakan meliputi kondensasi data, penyajian data, dan penarikan kesimpulan/verifikasi. Uji keabsahan data dilakukan melalui uji kredibilitas yang mencakup triangulasi sumber, triangulasi teknik, triangulasi waktu, dan membercheck; uji validitas eksternal; dependabilitas; dan konfirmabilitas. Hasil penelitian menunjukkan bahwa, peran kepala sekolah dalam meningkatkan kinerja guru yaitu Kepala sekolah sebagai pemimpin yaitu membuat indikator keberhasilan, memberdayakan manajemen dan guru dan pemberian penghargaan/Rewards, kepala sekolah sebagai motivator melalui pemberian motivasi dan pembinaan disiplin tenaga kependidikan, kepala sekolah sebagai educator (pendidik) yaitu membuat target yang disepakati, melakukan sosialisasi target dan melengkapi fasilitas guru. Peran tersebut berpengaruh dalam peningkatan kinerja guru, walaupun belum maksimal dan masih perlu untuk dievaluasi dan kepala sekolah perlu terus meningkatkan kinerja guru demi majunya mutu pendidikan sekolah. Kata kunci : peran kepala sekolah, kinerja guru